PERANAN PENDAPATAN RIIL, TINGKAT BUNGA DAN INFLASI DALAM FUNGSI PERMINTAAN UANG - Soebagiyo, Daryono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
This writing to see problem of real income, inflation, and interest rate in money demand function. There are some perception similarities that money demand largely depends on the income or GNP (Gross National Product), besides other factors involved, like interest and inflation rates. However, to make and estimation about money demand in and economic system, it will involved some interrelated problems. (I) The definition of the most suitable money, (2) argumentation about money demand function, (3) the stability of the function statistically from period to period.The writer persons a study model from M. Semudram with OLS (Ordinary Least Square) method towards function in the form of log linear where the variable inserted is the demanded sum of nominal money, consumers price index, nominal GNP, interest rate, and inflation rate.